PHARMACEUTICAL WORLD OF PERMEATION ENHANCERS - KUMAR, MANISH; PRASHAR, DEEPAK (International Journal of Current Pharmaceutical Research, 2021)
The drugs with poor solubility results in delayed absorption which consequently affects the bioavailability. There are many drugs which are having good therapeutic value but not used commercially because of this reason. The permeation enhancers are therefore being utilized to counter this problem. There are many such synthetic and natural materials which have the ability to enhance the drug permeation rate. The essential oils, alcohols, terpenes, azoles and many other chemical derivatives have the capability to be used for permeation enhancer. The present review work suggested the role of permeation enhancer in the pharmaceutical world.